PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN PRETASI BELAJAR SISWA PADA PEMBELAJARAN PERBANKAN DASAR DI KELAS X AKL-1 SMK NEGERI 1 KABANJAHE TAHUN PELAJARAN 2018/2019 (JS (JURNAL SEKOLAH), 2021)
Abstract: This study aims to determine the increase in student achievement and learning activities in basic banking learning the subject matter of current account deposits by applying the jigsaw type cooperative learning model in class X AKL-1 SMK Negeri 1 Kabanjahe in the 2018/2019 school year. This research is a classroom action research with two cycles. The place of research is SMK Negeri 1 Kabanjahe with the subjects in the study being all students of class X AKL-1 SMK Negeri 1 Kabanjahe for the academic year 2018/2019, totaling 32 students. In the study, student learning activities were obtained through observation of student activities in teaching and learning activities (KBM) while learning achievement of current account deposits was obtained through formative tests. The results of this study indicate; 1) student learning achievement increases by applying the jigsaw cooperative learning model in Formative I shows an average of 69 with 63% classical completeness and in Formative II shows an average of 81 with 88% classical completeness or an increase of 35%, the data shows an increase and achieve indicators of research success; 2) student learning activities increase by applying the jigsaw type cooperative learning model as indicated by the percentage of active students in Cycle I of 69% and in Cycle II of 88% with an increase of 19%.Keywords: Jigsaw, Learning AchievementAbstrak: Penelitian ini bertujuan untuk mengetahui peningkatan prestasi dan aktivitas belajar siswa pada pembelajaran perbankan dasar materi pokok simpanan dana giro dengan menerapkan model pembelajaran kooperatif tipe jigsaw di kelas X AKL-1 SMK Negeri 1 Kabanjahe tahun pelajaran 2018/2019. Penelitian ini adalah penelitian tindakan kelas dengan dua siklus. Tempat penelitian adalah SMK Negeri 1 Kabanjahe dengan subjek dalam penelitian adalah seluruh siswa kelas X AKL-1 SMK Negeri 1 Kabanjahe tahun pelajaran 2018/2019 yang berjumlah 32 siswa. Dalam penelitian, aktivitas belajar siswa diperoleh melalui observasi aktivitas siswa dalam kegiatan belajar mengajar (KBM) sedangkan prestasi belajar materi simpanan dana giro diperoleh melalui tes formatif. Hasil penelitian ini menunjukkan; 1) prestasi belajar siswa meningkat dengan menerapkan model pembelajaran kooperatif tipe jigsaw pada Formatif I menunjukkan rata-rata 69 dengan ketuntasan kalsikal 63% dan pada Formatif II menunjukkan rata-rata 81 dengan ketuntasan klasikal 88% atau terjadi peningkatan 35%, data tersebut menunjukkan peningkatan dan mencapai indikator keberhasilan penelitian; 2) aktivitas belajar siswa meningkat dengan menerapkan model pembelajaran kooperatif tipe jigsaw ditunjukkan dengan persentase siswa aktif Siklus I sebesar 69% dan pada Siklus II sebesar 88% dengan peningkatan 19%.Kata Kunci: Jigsaw, Prestasi Belajar